THE ROLE OF FINANCIAL LEVERAGE IN CORPORATE FINANCE - Pandya Nirza Shailendra; Dr. Nirav Gajjar (International Educational Journal of Science and Engineering, 2026)
Financial leverage, the strategic use of borrowed funds to finance the acquisition of assets, remains one of the most fundamental and widely debated concepts in corporate finance. This systematic literature review explores the evolution, theoretical frameworks, and practical implications of financial leverage on corporate performance and valuation. Through a comprehensive examination of foundational theories—including the Modigliani-Miller theorem, Trade-off Theory, Pecking Order Theory, and Agency Theory—this paper synthesizes decades of academic research to understand how firms navigate the complex trade-off between the tax shields associated with debt and the potential costs of financial distress. Furthermore, the review investigates the determinants of capital structure, analyzing how firm-specific characteristics and macroeconomic environments influence leverage decisions. By synthesizing existing literature, this paper highlights that there is no universal optimal capital structure; rather, leverage acts as a double-edged sword that can either magnify returns for shareholders or exacerbate bankruptcy risks during economic downturns. This review provides a clear, simple English synthesis of complex financial dynamics, offering valuable insights for researchers, corporate managers, and financial analysts.